2019
DOI: 10.29244/jam.6.2.129-138
|View full text |Cite
|
Sign up to set email alerts
|

Literature Review Filantropi Islam antara Tahun 2008 hingga 2018

Abstract: The author is interested in reviewing Islamic philanthropic literature between 2008 and 2018 because Islamic philanthropic behavior is found in any community, from the scope of the poorest countries to even the developed world. In addition, Islamic philanthropy is an object of study that has been widely studied in the social and economic fields. Articles about Islamic philanthropy were obtained using the zakat keyword on Emerald Insight between 2008 and 2018. The search results of 37 articles were then grouped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
0
6
0
2
Order By: Relevance
“…23 Islamic philanthropy is an object of study that is widely studied in the social and economic fields. 24 Islamic philanthropy is a topic that economists and researchers, both Muslims and non-Muslims, widely discussed. 25 That is because Islamic philanthropy is the most realistic way to reduce poverty and social inequality today.…”
Section: Results and Discussion Zakat Infaq Sadaqah And Waqf In Indon...mentioning
confidence: 99%
See 1 more Smart Citation
“…23 Islamic philanthropy is an object of study that is widely studied in the social and economic fields. 24 Islamic philanthropy is a topic that economists and researchers, both Muslims and non-Muslims, widely discussed. 25 That is because Islamic philanthropy is the most realistic way to reduce poverty and social inequality today.…”
Section: Results and Discussion Zakat Infaq Sadaqah And Waqf In Indon...mentioning
confidence: 99%
“…However, the management of the potential for Islamic philanthropic funds has not been optimal, hindering the achievement of this goal. 26 The author will dissect one -Islamic philanthropy, and the first is Zakat. Zakat aims to increase economic growth and community prosperity.…”
Section: Results and Discussion Zakat Infaq Sadaqah And Waqf In Indon...mentioning
confidence: 99%
“…Most topics of Zakat Research are about poverty. This topics was written by Effendi, 2017;Thalib et al, 2017;Rohman et al, 2017;Nisthar et al, 2017;Romdhoni, 2017;Alviana, 2018;Suryanto, 2018;Ayunniyah, 2018;Furqani et al, 2018;Purwatiningsih and Yahya, 2018;Ahmad et al, 2019;Musta'anah and Imam, 2019;Aminudin et al, 2019;Hassa, 2007;Shirazi and Amin, 2006;Toor and Nasar, 2004;Al Arif, 2013;Al Mubarak, 2016;Abdussalam et al, 2015; Adzrie et al, 2012; Ahmad et al, 2016; Aisyah, 2014; Ariyani, 2016; Ayuba, 2016; Bilhaq and Royyan, 2015; Table 1: Hassa, 2010; Ismail and Bayu, 2013;Johari et al, 2014;Malik, 2016;Muttaqin and Al Banna, 2015;Olanipekun, 2015;Qasim, 2016;Puspitasari et al, 2016;Raimi, 2015;Shirazi, 2014;Suheera, 2015;Tlemsani and Matthews, 2013;Uddin, 2016;Ahmed et al, 2017;Ayuniyyah et al, 2017;Gündoğdu, 2019;Ayuniyyah et al, 2018;Bhari et al, 2018;Nisthar et al, 2018.…”
Section: Development Of Main Topics Of Zakah Research Discussionmentioning
confidence: 99%
“…The results showed that the number of agricultural studies indexed by Scopus has increased significantly from year to year, since 1995-2015. Purwatiningsih & Yahya (2019) used a literature review study to find out islamic philanthropic literature during the period 2008 to 2018. This activity is widely found in the sphere of society and the state.…”
Section: Literature Reviewmentioning
confidence: 99%